2020
DOI: 10.1002/nme.6534
|View full text |Cite
|
Sign up to set email alerts
|

A novel accurate and computationally efficient integration approach to viscoplastic constitutive model

Abstract: A novel, accurate, and computationally efficient integration approach is developed to integrate small strain viscoplastic constitutive equations involving nonlinear coupled first-order ordinary differential equations. The developed integration scheme is achieved by a combination of the implicit backward Euler difference approximation and the implicit asymptotic integration. For the uniaxial loading case, the developed integration scheme produces accurate results irrespective of time steps. For the multiaxial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The unrealistic deformation only with the elastic deformation behavior is described by the existing overstress model in the impact loading, so that the existing overstress model is inapplicable to the description of the viscoplastic deformation behavior at high strain rate. Equation (21) with Equation ( 22) is extended so as to describe the viscoplastic deformation behavior adequately even at high strain rate by incorporating the term…”
Section: Subloading-overstress Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The unrealistic deformation only with the elastic deformation behavior is described by the existing overstress model in the impact loading, so that the existing overstress model is inapplicable to the description of the viscoplastic deformation behavior at high strain rate. Equation (21) with Equation ( 22) is extended so as to describe the viscoplastic deformation behavior adequately even at high strain rate by incorporating the term…”
Section: Subloading-overstress Modelmentioning
confidence: 99%
“…15,16 In addition, the numerical methods for viscoplasticity models have been developed in past studies. [17][18][19][20][21] Here, the creep model is insufficient to describe the elastoplastic deformation behavior observed at the quasi-static loading process because it possesses the basically different structure from that of the elastoplasticity model based on the yield surface. In fact, the creep model predicts the viscoplastic deformation for any low stress level since it does not possess the threshold value of stress for the occurrence of viscoplastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of avoiding the increase of computational cost, the approaches to express the equations to be solved by a single scalar formulation have been established (De Angelis and Taylor, 2015; Wali et al ., 2015). These approaches have been extended to a non-associated anisotropic plasticity (Wali et al ., 2016; Bouhamed et al ., 2019) and a viscoplasticity (Kumar and Patel, 2021; De Angelis, 2022). Other approaches to reduce the computational cost of the return mapping algorithm include a state update algorithm (Nodargi and Bisegna, 2016; Nodargi, 2019) and a novel iterative scheme (Magisano and Corrado, 2023) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Large trial stress state with good convergence for return mapping method was shown by a line search algorithm (Scherzinger, 2017). Combined integration schemes have also been attempted (Kumar and Patel, 2021) with relatively large time increments with limited loss of accuracy. The non-Newtonian methods reviewed here have not been applied for steam turbine or any particular industrial engineering application.…”
Section: Introductionmentioning
confidence: 99%